The Relative Age Effect and Talent Identification Factors in Youth Volleyball in Poland - Rubajczyk, Krystian; Rokita, Andrzej (Frontiers in Psychology, 2020)
Previous studies in team sports have not reported evidence regarding the relative age effect (RAE) in relation to the talent identification (TI) process in volleyball, which is organized and controlled by a national federation. Volleyball is a noncontact team sport in which a player's physique does not directly affect other players in the game but is considered one of the most critical factors in the TI process. The aims of the present study were (1) to determine the differences in the quarterly distribution of age between Polish youth volleyball players from the Olympic Hopes Tournament (OHT) and the general population, (2) to investigate the quarterly differences in anthropometric characteristics and motor test results in OHT participants and (3) to identify the criteria that determine selection for the National Volleyball Development Program (NVDP). The present study identified the RAE in young male (n = 2528) and female (n = 2441) Polish volleyball players between 14 and 15 years of age who competed in the elite OHT in 2004-2015. The study included anthropometric characteristics, motor test results, and selection for the NVDP. In the group of nonselected NVDP male players, the analysis demonstrated significant differences by birth quarter as a covariate for body height (F=0.01), p<0.001), spike reach (F=7.33), p<0.05) and block jump (F=0.02, p<0.001). Significant differences by calendar age as a covariate were observed for body mass (F=0,53), p<0,01), spike jump (F=2,64), p<0.05), block jump (F=0.4) p<0.01) and zigzag agility test results (F =0.01, p<0.01). The results showed a significant overrepresentation of early-born participants in the OHT and NVDP subsamples. The classification model demonstrated that a combination of four characteristics optimally discriminated between players selected for the NVDP and those who were not selected. This combination of variables correctly classified 77.7% of the female players and 71.8% of the male players in terms of their selection for the NVDP. The results of this study show that jumping ability and body height are crucial in the TI and selection process in youth volleyball.